Blended Learning in Nepalese Higher Education: A Qualitative Study of Current Practices and Emerging Trends - Basnet, Hom Bahadur; Rai, Pradeep; Parajuli, Kewal Ram (Journal of Research and Development, 2025)
This study examines the evolving preferences of students and changes in the mode of teaching and learning over time, recognizing the need to address student demands for effective education. The primary objectives are to identify shifting student preferences regarding learning modes and to analyze the current practices and applied modalities of blended learning. Specifically, the integration between face-to-face and online instruction. Through a systematic review of literature and informal interviews, the study finds an increasing student attraction to blended learning, corresponding with a growth in the number of academic programs adopting this approach. Among the 11 observed universities (Acharya et al., 2022) , three have already launched academic programs in a blended mode, and all programs offered by Nepal Open University (NOU) are entirely blended structure. Due to the benefits of blended learning mode such as multisensory engagement and time flexibility. it is recommended that Nepalese universities need to prioritize the development of policies and programs related to extension of blended learning mode to effectively meet student demand and needs.